The role of TGFβ1 and LRG1 in cardiac remodelling and heart failure - Song, Weihua (2015)
Heart failure is a life-threatening condition that carries a considerable emotional and socio-economic burden. As a result of the global increase in the ageing population, sedentary life-style, increased prevalence of risk factors, and improved survival from cardiovascular events, the incidence of heart failure will continue to rise. Despite the advances in current cardiovascular therapies, many patients are not suitable for or may not benefit from conventional treatments. Thus, more effective therapies are required. Transforming growth factor (TGF) β family of cytokines is involved in heart development and dys-regulated TGFβ signalling is commonly associated with fibrosis, aberrant angiogenesis and accelerated progression into heart failure. Therefore, a potential therapeutic pathway is to modulate TGFβ signalling; however, broad blockage of TGFβ signalling may cause unwanted side effects due to its pivotal role in tissue homeostasis. We found that leucine-rich α-2 glycoprotein 1 (LRG1) promotes blood vessel formation via regulating the context-dependent endothelial TGFβ signalling. This review will focus on the interaction between LRG1 and TGFβ signalling, their involvement in the pathogenesis of heart failure, and the potential for LRG1 to function as a novel therapeutic target.